Kristen Progresif: Analisis Kritis Terhadap Penyimpangan Teologis dalam Pemikiran Modern - Ari Wibowo, Daniel (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2024)
Progressive Christianity has emerged as one of the significant streams of thought in modern theology. This movement seeks to reinterpret Christian teachings by incorporating contemporary social and cultural values. However, the evolving understanding of Progressive Christianity often sparks debates over deviations from established orthodoxy and traditional Christian practices. This article aims to critically analyze Progressive Christianity, focusing on the theological deviations present in these new interpretations. The study explores the impact of progressive thought on the core principles of Christian faith and its consistency with traditional teachings. This research employs a qualitative approach using literature analysis methods. Primary and secondary sources relevant to Progressive Christianity and traditional Christian theology are critically examined to identify significant doctrinal changes and shifts. The findings reveal that Progressive Christianity tends to adopt secular values and flexible moral interpretations, often conflicting with traditional teachings. Certain concepts within Progressive Christianity, such as the reinterpretation of the Bible and fundamental doctrines, are seen as potentially diluting the core of Christian faith. Progressive Christianity presents a significant challenge to Christian orthodoxy by attempting to merge modern thought and contemporary interpretations into theology. This analysis indicates that while there is an intent to make the Christian faith more relevant to the modern world, such thinking can lead to deviations from the true foundations of Christian faith.